2018
DOI: 10.1001/jamainternmed.2018.0292
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metformin Use With Risk of Lactic Acidosis Across the Range of Kidney Function

Abstract: IMPORTANCE Approximately 1 million patients in the United States with type 2 diabetes mellitus and mild-to-moderate kidney disease do not receive guideline-directed therapy with metformin. This may reflect uncertainty regarding the risk of acidosis in patients with chronic kidney disease. OBJECTIVE To quantify the association between metformin use and hospitalization with acidosis across the range of estimated glomerular filtration rate (eGFR), accounting for change in eGFR stage over time. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
1
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 42 publications
6
131
1
6
Order By: Relevance
“…The incidence rates of acidosis in people with CKD stage 2 (eGFR 60–89 mL/min/1.73m 2 ), 3A (eGFR 45–59 mL/min/1.73m 2 ), 3B (eGFR 30–44 mL/min/1.73m 2 ), and 4–5 (eGFR ≤ 30 mL/min/1.73m 2 ) were 4, 7, 10, and 24 per 1000 person‐years, respectively. These results were reproducible when new metformin users were compared with new sulfonylurea users, in propensity score‐matched cohort, and in the replication cohort of 82 017 people from a nationwide database . Similarly, a Taiwanese population‐based, observational cohort study demonstrated that metformin use was associated with a 35% higher risk of all‐cause mortality in people with type 2 diabetes and serum creatinine concentrations greater than 530 μmol/L (equivalent to end‐stage kidney disease) .…”
Section: Metformin Use and The Risk Of Lactic Acidosis In People Withmentioning
confidence: 63%
See 1 more Smart Citation
“…The incidence rates of acidosis in people with CKD stage 2 (eGFR 60–89 mL/min/1.73m 2 ), 3A (eGFR 45–59 mL/min/1.73m 2 ), 3B (eGFR 30–44 mL/min/1.73m 2 ), and 4–5 (eGFR ≤ 30 mL/min/1.73m 2 ) were 4, 7, 10, and 24 per 1000 person‐years, respectively. These results were reproducible when new metformin users were compared with new sulfonylurea users, in propensity score‐matched cohort, and in the replication cohort of 82 017 people from a nationwide database . Similarly, a Taiwanese population‐based, observational cohort study demonstrated that metformin use was associated with a 35% higher risk of all‐cause mortality in people with type 2 diabetes and serum creatinine concentrations greater than 530 μmol/L (equivalent to end‐stage kidney disease) .…”
Section: Metformin Use and The Risk Of Lactic Acidosis In People Withmentioning
confidence: 63%
“…The data on the safety of metformin in mild to moderate renal impairment (eGFR 30–60 mL/min/1.73m) have been limited until recently and sometimes conflicting, despite increased laxity in prescribing guidelines. Recent studies provide further evidence that metformin does not appear to increase the risk of lactic acidosis in mild to moderate renal impairment . However, prescribing metformin in people with moderate to severe renal impairment remains a controversial issue and this is reflected in the conflicting advice in the different international prescribing guidelines (Box 1), with some authorities providing more conservative advice.…”
Section: Resultsmentioning
confidence: 99%
“…Another study published in July 2018 looked at metformin use in a real-world setting [14]. It had a community-based cohort of 75,000 diabetic patients within the Geisinger Health System in the USA.…”
Section: Diabetic Nephropathy: Hiddo Lambers Heerspink (The Netherlands)mentioning
confidence: 99%
“…1 In 2016, the USA Food and Drug Administration (FDA) changed the recommendations for metformin for diabetes to expand its use in certain patients with reduced kidney function. 2 However, despite this and other changes to metformin labelling, it was thought that many people may be missing out on the possible benefits of treatment with metformin because of persisting concerns over drug accumulation and lactic acidosis.…”
mentioning
confidence: 99%
“…1 It included 75,413 people with diabetes registered with a primary healthcare organisation in Pennsylvania USA, with assessment of eGFR from January 2004 until January 2017. The authors also used data on 67,578 new metformin users and 14,439 new sulfonylurea users from 350 private USA health systems, to replicate the results.…”
mentioning
confidence: 99%